Artificially phase separated ternary self-assembled monolayers composed of 11-aminoundecanethiol, 1-dodecanethiol and 10-carboxy-1-decanethiol on Au(111) prepared by electrochemically selective replacement technique - Phong, Pham Hong (Vietnam Journal of Chemistry, 2015)
The template ternary self-assembled monolayer composed of 11-amino-1-undecanethiol (AUT), 1-dodecanthiol (DDeT) and 2-hydroxyethanethiol (MEL) prepared by coadsorption method forms two types of domain in nano meter scale on Au(111): one mainly composed of AUT and DDeT, the other mainly composed of MEL. After replacing MEL with 10-carboxy-1-decanethiol (CDT) by use of electrochemically selective replacement technique, the final ternary SAMs of AUT-DDeT-CDT composed of AUT-DDeT domains and CDT domains having similar alkyl chain length have been obtained. Results also indicate that the presence of adsorbed DDeT molecules enhances the phase separation between AUT-DDeT and CDT domains. This can be explained by the increase in the surface activities of hydrophobic DDeT in the AUT-DDeT domains of the final ternary SAMs.